2016
DOI: 10.1007/s00261-016-0811-y
|View full text |Cite
|
Sign up to set email alerts
|

MR comparative study of combined hepatocellular-cholangiocarcinoma in normal, fibrotic, and cirrhotic livers

Abstract: MRI may provide valuable information for the diagnosis and differential diagnosis of cHCC-CC in normal, fibrotic, and cirrhotic livers. The nodule size, enhancement pattern, and the presence of mosaic architecture in cHCC-CC differ between different degrees of background liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…As has previously been reported, 19,20 our study demonstrated that the mean tumour size of cHCC‐CCAs was significantly smaller in patients with cirrhosis than in those without cirrhosis. This finding may be explained by the more frequent imaging‐based liver surveillance performed in patients with cirrhosis, enabling detection of smaller‐sized tumours.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As has previously been reported, 19,20 our study demonstrated that the mean tumour size of cHCC‐CCAs was significantly smaller in patients with cirrhosis than in those without cirrhosis. This finding may be explained by the more frequent imaging‐based liver surveillance performed in patients with cirrhosis, enabling detection of smaller‐sized tumours.…”
Section: Discussionsupporting
confidence: 87%
“…Our study results, with 67.3% of cHCC‐CCAs categorized as LR‐M, also fell within this range 8‐10,21,22 . Several studies have also reported that imaging features associated with cHCC‐CCAs can vary depending on the liver background 19,23 . For example, Sheng et al reported that an HCC‐like enhancement pattern (ie arterial phase hyperenhancement with washout on portal venous or delayed phases) was observed more frequently in patients with cHCC‐CCAs associated with cirrhosis than in those without cirrhosis 19 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although pathologic diagnosis for PLC is required in patients without any risk factors for HCC development, it is important to evaluate the applicability and performance of these diagnostic imaging guidelines in these patients as it may provide insight for different imaging features of cHCC-CCA according to the presence of risk factors. For example, cHCC-CCA arising in cirrhotic liver was more likely to resemble imaging features of HCC than that arising in non-cirrhotic liver (45). Furthermore, different priorities in treatment practices among guidelines should also be taken into account when adapting these imaging guidelines to PLCs other than HCCs (46).…”
Section: Remaining Issuesmentioning
confidence: 99%
“…A few studies have evaluated the imaging characteristics of CHC based on contrast-enhanced computed tomography (CECT) [8,9] and magnetic resonance imaging (MRI) [8,10,11]. Theoretically, because CHC comprises HCC and CC components, the imaging features of both HCC and CC would be visualized, with either an HCC-like or CC-like appearance predominating [8].…”
Section: Introductionmentioning
confidence: 99%